2004
DOI: 10.1097/01.olq.0000124611.73009.d5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Urine Testing in Evaluations of the Sensitivity of the Gen-Probe APTIMA??Combo 2 Assay on Endocervical Swabs for Chlamydia trachomatis and Neisseria gonorrhoeae

Abstract: The infected patient standard reduces the sensitivity of the endocervical evaluation because some infected patients are positive only with FCU. The reduction in sensitivity is greater when testing for CT. Specificities improved slightly, because some unique cx positives, initially classified as false-positive were confirmed by a positive FCU result. Sensitivity of AC2 was higher than LCR, PCR, and culture. Specificity was slightly lower, but discrepant analysis (using alternate TMA targets) of apparent AC2 fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
36
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 21 publications
3
36
1
1
Order By: Relevance
“…5,6,13 • NAATs are more sensitive than culture, offer testing on a wider range of specimen types and are less demanding in specimen quality, transportation and storage. [17][18][19][20][21][22][23][24][25] They show high sensitivity (>96%) in both symptomatic and asymptomatic infection, show equivalent sensitivity in urine and urethral swab specimens from men 23 and equivalent sensitivity in clinician-taken or self-taken vulvo-vaginal and endocervical swabs from women. 24 NAATs significantly outperform transported samples for culture and are the sample of choice for testing individuals who are asymptomatic.…”
Section: Diagnosismentioning
confidence: 99%
“…5,6,13 • NAATs are more sensitive than culture, offer testing on a wider range of specimen types and are less demanding in specimen quality, transportation and storage. [17][18][19][20][21][22][23][24][25] They show high sensitivity (>96%) in both symptomatic and asymptomatic infection, show equivalent sensitivity in urine and urethral swab specimens from men 23 and equivalent sensitivity in clinician-taken or self-taken vulvo-vaginal and endocervical swabs from women. 24 NAATs significantly outperform transported samples for culture and are the sample of choice for testing individuals who are asymptomatic.…”
Section: Diagnosismentioning
confidence: 99%
“…This is because some infected patients may have one specimen positive only. 76 Differences in the analytical sensitivities of NAAT assays may also create complications for such evaluations. By using TMA technology to amplify rRNA, the Gen-Probe AC2 assay has in theory the potential to detect lower concentrations of N. gonorrhoeae because the copies of 16S rRNA will usually exceed that of DNA targets used by other commercial N. gonorrhoeae NAATs.…”
Section: Issues For Assay Validationmentioning
confidence: 99%
“…However, recent studies showed that nucleic acid amplification-based N. gonorrhoeae tests (NAATs) are much more sensitive (1,2,4,6,7,10). The Roche COBAS AMPLICOR (CA) N. gonorrhoeae test is probably the most widely used amplification test for N. gonorrhoeae.…”
mentioning
confidence: 99%